(untitled) (Modern education and development, 2025)
Word formation plays a crucial role in enabling languages to evolve and respond to the shifting communicative demands of their users. In modern linguistic contexts, it serves not only as a means of grammatical development but also as a channel for expressing creativity, innovation, and cultural depth. This paper examines the expressive aspects of word formation by analyzing key processes including affixation, compounding, blending, clipping, lexical borrowing, and semantic change. Through comprehensive analysis and practical examples, the research demonstrates how newly coined words enrich linguistic expression, reflect social identities, and shape contemporary digital communication.